2021
DOI: 10.1038/s41467-021-27106-w
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and phenotypic profiling of colorectal cancer patients in West Africa reveals biological insights

Abstract: Understanding the molecular and phenotypic profile of colorectal cancer (CRC) in West Africa is vital to addressing the regions rising burden of disease. Tissue from unselected Nigerian patients was analyzed with a multigene, next-generation sequencing assay. The rate of microsatellite instability is significantly higher among Nigerian CRC patients (28.1%) than patients from The Cancer Genome Atlas (TCGA, 14.2%) and Memorial Sloan Kettering Cancer Center (MSKCC, 8.5%, P < 0.001). In microsatellite-stable ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 33 publications
2
37
0
Order By: Relevance
“…Only three studies in sub-Saharan Africa have attempted to further differentiate between subgroups within the overarching category of MSI tumours. Alatise et al found the rate of MSI in their Nigerian cohort to be more than double that reported in HIC 13. However, germline testing on a subset of the cases found pathogenic mutations to be present in only 17% of the MSI-H cases, which is similar to internationally reported rates (11–18.5%) 39 48.…”
Section: Crc In Africasupporting
confidence: 57%
See 4 more Smart Citations
“…Only three studies in sub-Saharan Africa have attempted to further differentiate between subgroups within the overarching category of MSI tumours. Alatise et al found the rate of MSI in their Nigerian cohort to be more than double that reported in HIC 13. However, germline testing on a subset of the cases found pathogenic mutations to be present in only 17% of the MSI-H cases, which is similar to internationally reported rates (11–18.5%) 39 48.…”
Section: Crc In Africasupporting
confidence: 57%
“…These include a younger age of onset, more advanced disease at presentation, increased mucinous differentiation and increased frequency of microsatellite instability (MSI). More recently, larger studies have shown an increased frequency of left-sided tumours among young indigenous Africans 12 13. This is in contrast to data from Europe, Japan and the USA, which shows decreasing frequency of left-sided disease 14–16…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations